2019
DOI: 10.1007/s10551-019-04342-1
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Political Strategies in Weak Institutional Environments: A Break from Conventions

Abstract: There is a lack of research about the political strategies used by firms in emerging countries, mainly because the literature often assumes that Western-oriented corporate political activity (CPA) has universal application. Drawing on resourcedependency logics, we explore why and how firms orchestrate CPA in the institutionally challenging context of Nigeria. Our findings show that firms deploy four context-fitting but ethically suspect political strategies: affective, financial, pseudoattribution and kinship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 155 publications
0
34
0
Order By: Relevance
“…The quality of regulatory institutions is measured by how a country develops, implements, and enforces legislation and regulations that affect businesses and industries (Liedong, Aghanya, & Rajwani, 2020). Researchers have suggested that regulatory quality plays a large role in shaping managerial decision‐making (Liedong et al, 2020) because it codifies society's expectations and preferences regarding the power and autonomy of organizations and their managers (North, 1990; Scott, 1995). CEOs embedded in institutions with a high regulatory quality face less uncertainty; however, such institutions have more standardizing practices and demand more conformity (Holmes Jr et al, 2013).…”
Section: Theory and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The quality of regulatory institutions is measured by how a country develops, implements, and enforces legislation and regulations that affect businesses and industries (Liedong, Aghanya, & Rajwani, 2020). Researchers have suggested that regulatory quality plays a large role in shaping managerial decision‐making (Liedong et al, 2020) because it codifies society's expectations and preferences regarding the power and autonomy of organizations and their managers (North, 1990; Scott, 1995). CEOs embedded in institutions with a high regulatory quality face less uncertainty; however, such institutions have more standardizing practices and demand more conformity (Holmes Jr et al, 2013).…”
Section: Theory and Hypotheses Developmentmentioning
confidence: 99%
“…For instance, in nations with high regulatory quality, such as the United States, Canada, and many nations of the European Union, adherence to regulatory policies is both expected and strictly enforced. Thus, executive latitude in decision‐making is constrained (Duran, Van Essen, Heugens, Kostova, & Peng, 2019; Liedong et al, 2020). In contrast, in institutions with low regulatory quality, policies lack legitimacy, and corporate compliance is neither expected nor effectively enforced (Campbell, 2007).…”
Section: Theory and Hypotheses Developmentmentioning
confidence: 99%
“…It is possible for entrepreneurs with no ethnic or party alignment to access government support. In fact, extant research on political connections has documented the role of personal political ties in accessing government support (e.g., Liedong et al, 2020;Zheng et al, 2015). Therefore, this study advances a more complete understanding of access to government support by examining the roles of entrepreneurial identity (i.e., ethnic and political).…”
Section: Boundary Conditions and Foundations For Future Researchmentioning
confidence: 89%
“…These commitments often entail providing support (i.e., financial and/or nonfinancial) to the ruling political party or regime officials (Arriola, 2013;Beresford, 2015). Such reciprocation has been shown to increase the operational costs of ventures (Bertrand et al, 2018) and limit attention on market forces (Liedong et al, 2020), thereby undermining the ability of entrepreneurs to pursue innovative market opportunities or seek competitive advantage through distinctive customer value creation. Second, identity-based government support can foster a dependent mindset that is antithetical to entrepreneurial principles underlying market economies.…”
Section: Identity-based Government Support and Long-term Venture Perf...mentioning
confidence: 99%
“…But local engagement and a multi-stakeholder approach were found to be necessary later in the reform process. In a qualitative study of 13 banks in Nigeria, Liedong, Aghanya, and Rajwani (2020) found that firms use four CPA strategies: affective, financial, pseudo-attribution, and kinship strategies. The authors argue that these strategies can be context-fitting but ethically suspect at times.…”
Section: Predictors Of Cpamentioning
confidence: 99%